Problematika dan Tantangan Pendidikan Islam Serta Solusinya di Era Global - Amir Mirdad; Yurna Yurna; Hoerul Khusban; E. Komarudin; Muhamad Atep Saepul Rahman (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Islamic education in the global era faces various complex problems and challenges, ranging from conventional teaching methods, varying teacher quality, to curriculum unpreparedness in addressing social and technological dynamics. The globalization of information and culture also significantly influences students’ behavior and identity, requiring digital literacy, critical cultural awareness, and resilience in religious values to remain aligned with Islamic principles. This study employs a library research approach with a descriptive qualitative method, analyzing various books and scientific journals related to Islamic education in the global era. The findings indicate that the problems of Islamic education include the gap between traditional methods and 21st-century needs, teachers’ unpreparedness in using technology, and the lack of integration between religious education and contemporary social contexts. Other challenges involve education management, family and community involvement, and policy-making that responds to global changes. To address these issues, recommended solutions include revitalizing an integrative curriculum that combines Islamic values with 21st-century skills, utilizing technology wisely, enhancing teacher competence, strengthening collaboration between schools, families, and communities, and developing media literacy and inclusive pedagogical approaches. Implementing these strategies is expected to produce students who are competent, adaptive, character-driven, and globally competitive without losing their moral and spiritual identity. These findings contribute to the development of Islamic education that is relevant, adaptive, and sustainable in the global era.